2010
DOI: 10.1016/j.jtcvs.2010.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes of deliberate nonoperative management for blunt thoracic aortic injury in trauma

Abstract: This experience suggests that deliberate, nonoperative management of carefully selected patients with traumatic blunt aortic injury may be a reasonable alternative in the polytrauma patient; however, serial imaging and long-term follow-up are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…More broadly, these results are consistent with the safety of delayed repair or nonoperative treatment for patients with limited pseudoaneurysms and minimal secondary signs of injury, particularly as a relatively large subgroup of stable patients was treated without aortic intervention. 9,10,16 In contrast, although higher lactate levels are associated with organ failure and death after major trauma, 27 the relationship among lactate, BTAI severity, and lesion stability is unclear. Short of frank rupture, large aortic lesions could potentially contribute to systemic malperfusion through altered flow dynamics 28 or result in tension or tamponade physiology from extensive mediastinal hemorrhage or hematoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More broadly, these results are consistent with the safety of delayed repair or nonoperative treatment for patients with limited pseudoaneurysms and minimal secondary signs of injury, particularly as a relatively large subgroup of stable patients was treated without aortic intervention. 9,10,16 In contrast, although higher lactate levels are associated with organ failure and death after major trauma, 27 the relationship among lactate, BTAI severity, and lesion stability is unclear. Short of frank rupture, large aortic lesions could potentially contribute to systemic malperfusion through altered flow dynamics 28 or result in tension or tamponade physiology from extensive mediastinal hemorrhage or hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…9,[15][16][17] Although some scales incorporate BTAI size and secondary signs of aortic injury, such as mediastinal hematoma, none include patient physiology or assess the stability of the lesion. As such, none of the current systems quantify a lesion's risk of rupture.…”
mentioning
confidence: 99%
“…24 Follow-up imaging of minimal aortic injuries indicates a high rate of resolution and low rate of progression to more severe injury. 23,[25][26][27][28][29][30] For example, in a series of 43 patients with low-grade lesions and medium-term followup imaging reported by Osgood et al, 55% of lesions resolved and 40% remained stable. Progression to a higher grade injury occurred in two patients, but late intervention was not required.…”
Section: Lesion Assessment and Risk Stratificationmentioning
confidence: 99%
“…3,17,32,33 Whereas pseudoaneurysms are associated with aortic-related morbidity and mortality because of greater potential for progression to rupture, 3,10,17 some remain stable and have been successfully managed nonoperatively. 10,16,29,30,[34][35][36] For example, Rabin et al reported a nonoperative management rate of 28% (17/59) for uncomplicated pseudoaneurysms, with no aortic mortality. 35 Similarly, in preliminary data from Osgood et al, 24% (37/153) of patients with pseudoaneurysms were managed medically, although one patient with a larger lesion subsequently ruptured and died.…”
Section: Lesion Assessment and Risk Stratificationmentioning
confidence: 99%
See 1 more Smart Citation